The name of this band is R.E.M. : a biography - Carlin, Peter Ames (Doubleday, 2024)
"In the spring of 1980, an unexpected group of musical eccentrics came together to play their very first performance at a college party in Athens, Georgia. Within a few short years, they had taken over the world – with smash records like Out of Time, Automatic for the People, Monster and Green. Raw, outrageous, and expressive, R.E.M.’s distinctive musical flair was unmatched, and a string of mega-successes solidified them as generational spokesmen. In the tumultuous transition between the wide-open 80s and the anxiety of the early 90s, R.E.M. challenged the corporate and social order, chasing a vision and cultivating a magnetic, transgressive sound. In this rich, intimate biography, critically acclaimed author Peter Ames Carlin looks beyond the sex, drugs, and rock’n’roll to open a window into the fascinating lives of four college friends – Michael Stipe, Peter Buck, Mike Mills and Bill Berry – who stuck together at any cost, until the end. Deeply descriptive and remarkably poetic, steeped in 80s and 90s nostalgia, The Name of This Band is R.E.M. paints a cultural history of the commercial peak and near-total collapse of a great music era, and the story of the generation that came of age at the apotheosis of rock."--